URGENSI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN ISLAM - Supriani, Supriani (ILJ: Islamic Learning Journal, 2024)
Human resources (HR) is one of the important factors in the development of Islamic education. This research uses library research, with documentary methods. The results of the study state that human resource development can be through training and research, training can make the human resources of Islamic education institutions more competent and professional while development aims to trigger human resources to channel their innovation and creativity. By going through the stages of planning, training and development design and evaluation, as well as development and training have an important role in helping to become wiser, able to solve problems, foster enthusiasm, reduce stress and frustration, increase job satisfaction, become more independent and hardworking and make more confident in facing the challenges of the times. So that when the Islamic education institution conducts development and training properly, it will produce good teaching and education personnel as well.